Height analysis of Rio swimming finalists - Madge, R. (2016)
This analysis includes the average, shortest and tallest heights of every final for 2016, as well as the average heights for 2012. The averages give us a decent amount of data for comparison, while the shortest and tallest heights help us determine the envelope of elite swimming.